"It's never too late to learn"–How does the Polish U3A change the quality of life for seniors?. Issue 3 (3rd March 2016) - Mackowicz, Jolanta; Wnek-Gozdek, Joanna
ABSTRACT: In the face of the ageing of society, the concept of active ageing has become a key problem within European politics. (United Nations, 2002; European Commission, 2006). In recent years, the University of Third Age (U3A) movement has developed very quickly both within Poland and outside our country. In this article, we consider the educational activity of Polish seniors and the influence this has had on their quality of life in selected areas. A qualitative research study was conducted in May 2015 among U3A participants. A collective case study was undertaken (Stake, 2009) to capture the changes in the quality of life in different areas (adaptation to changes, participation in social life, obtaining and providing support, activity, and lifelong education). (Escuder Mollon & Gil, 2014) Despite the undeniably positive influence on the quality of life among seniors the U3A is still not accessible for the average senior because of their location, their material conditions, and their individual readiness to take part in such activities. In Poland there is also a very strong tradition of engaging seniors in the care of their grandchildren, and this in many cases makes it impossible for them to take part in any self-development or self-actualization programs.